ROLE OF SOCIETY IN CONSERVATION OF NATURAL RESOURCES - Deo, Sandhya (International Journal of Research -GRANTHAALAYAH, 2015)
Anything in the environment which can be used is called a ‘natural resource’. Protecting the environment from destruction is called conservation of environment. Some of our important natural resources are forest, wildlife, water, coal & petroleum. The resources of the earth are limited because of the rapid increase in population. The demand for resources is increasing day by day. The proper management can ensure that the natural resources are used judiciously so that they fulfill the needs of present generation and also last for the generations to come. Water is the basic necessity for all forms of life, human beings other animals as well as plants. The various sources of water are: Rain, Rivers, Lakes, Ponds, Wells, Oceans and Glaciers. Rain is a very important source of water. Rains in India are largely due to monsoon which, lasts for a few months. High yielding Varieties of crops require more water for irrigation. The changing life style of people is consuming more water so we are not able to fulfill the demand of water for all people. Rivers are another important source of water. The management of river water is done by constructing dams on rivers. Dams are useful for the society because of irrigation, water supply in towns and cities, generating electricity. The public opposition on the construction of large dams on rivers is mainly due to some problems. Due to construction of dams a large number of human settlements are submerged in the water of large reservoir formed by the dam and many people are rendered homeless. It also contributes to deforestation and lose of biodiversity. The water of most of rivers is highly polluted. The pollution of river water is caused by the dumping of untreated sewage and industrial water into it. Wells and tube wells are other sources of water. This water is used for the irrigation of crops and for drinking purpose.